Effects of chronic stress on smartphone addiction: A moderated mediation model - Huake Qiu; Hongliang Lu; Jiawei Pei; Yajuan Zhang; Yongjie Ma; Chen Xing; Xinlu Wang; Xia Zhu (Frontiers Media S.A., 2023)
IntroductionBased on the compensatory Internet use theory and diathesis-stress model, the present study explores the effects of chronic stress on smartphone addiction (SPA). As intolerance of uncertainty and emotion-related variables are important factors that affect addictive behavior, we explore the mediating role of intolerance of uncertainty and the moderating role of emotion differentiation.MethodsWe conducted a questionnaire survey of 286 participants (13.64% female; Mage = 22.88; SD = 3.77; range = 17-39) on chronic stress, SPA, intolerance of uncertainty, and emotion differentiation. SPSS 28.0 was used to analyze the descriptive statistics and correlations and test the moderated mediation model.ResultsWe find that (1) intolerance of uncertainty, SPA, and chronic stress are positively correlated with each other. Positive emotion differentiation is positively correlated with intolerance of uncertainty and negative emotion differentiation. (2) Intolerance of uncertainty plays a mediating role in chronic stress and SPA. (3) Positive emotion differentiation significantly moderates the relationship between chronic stress and SPA. Under the condition of low positive emotion differentiation, chronic stress is more effective in predicting SPA.DiscussionThese findings may contribute to intervention and prevention programs for SPA. Thus, the intervention and prevention of SPA can start from two directions-reduce the intolerance of uncertainty and enhance the ability to experience positive emotion differentiation.